2022
DOI: 10.1210/clinem/dgac532
|View full text |Cite
|
Sign up to set email alerts
|

Twin Study: Genetic and Epigenetic Factors Affecting Circulating Adiponectin Levels

Abstract: Context Clarification of the association among phenotypes, genetic and environmental factors with clinical laboratory traits can reveal the cause of diseases and assist in developing methods for the prediction and prevention of diseases. It is difficult to investigate the environmental effect on phenotypes using individual samples because their genetic and environmental factors differ, but we can easily investigate the influence of environmental factors using monozygotic (MZ) twins because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Gene expression can be modified by epigenetic changes, which do not alter the DNA sequence [ 8 ]. The attachment of methyl groups to cytosine rings within guanine residues, a process called DNA methylation, is the most extensively investigated epigenetic modification due to its relative ease of measurement [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gene expression can be modified by epigenetic changes, which do not alter the DNA sequence [ 8 ]. The attachment of methyl groups to cytosine rings within guanine residues, a process called DNA methylation, is the most extensively investigated epigenetic modification due to its relative ease of measurement [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that lower levels of 5mdC/dG were related to higher levels of serum adiponectin. Previous studies have shown that epigenetic modifications can affect genes expression related to adiponectin [ 7 , 8 ]. A Japanese study involving 232 pairs of monozygotic twins conducted an epigenetic variation association study to identify epigenetic regulators influencing adiponectin levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insufficient consideration of confounding factors that may impact both protein levels and risk of infection in the neonatal period is another reason [7]. The twin design could control for shared genetic and environmental confounding factors and thus may enhance the strength of causal evidence in omics research [8].…”
Section: Introductionmentioning
confidence: 99%